Role of caste pressure groups in Indian politics: Analysis: भारतीय राजनीति में जातिगत दबाव समूहों की भूमिका: विश्लेषण - Saini, B.L; Sharma, Vikas Kumar; Kumar, Sunil (RESEARCH HUB International Multidisciplinary Research Journal, 2024)
The study of pressure, interests and organized groups and their techniques has special importance in the modern political process. This study throws light on the underlying forces and processes through which political power operates and is exercised in organized societies, especially in democratic societies. But this does not mean that pressure interest groups do not exist in a totalitarian system. The difference is that while in democratic societies these groups are considered healthy elements for political activity and these groups remain active in their own way to protect their vested interests, in totalitarian or communist societies these groups do not have their own independent importance. Rather, their position is only as instruments of the state whose purpose is to help in achieving the goals set by the state. Abstract in Hindi Lanaguage: आधुनिक राजनीतिक प्रक्रिया में दबाव, हित एवं संगठित समूहों तथा उनकी तकनीकों के अध्ययन का विशिष्ट महत्व हैं। इस अध्ययन से उन अन्तर्निहित शक्तियों और प्रक्रियाओं पर प्रकाश पड़ता है जिनके माध्यम से संगठित समाजों में विशेषकर लोकतांत्रिक समाजों में राजनीतिक शक्ति का संचालन और प्रयोग होता है। लेकिन इसका अभिप्राय यह नही है कि सर्वाधिकारवादी व्यवस्था में दबाव हित-समूहों का अस्तित्व नही होता। अंतर यही है कि जहाँ लोकतंत्रिक समाजों मे ये समूह राजनीतिक क्रियाशीलता के लिए स्वस्थ तत्व माने जाते है और अपने निहित स्वार्थों की रक्षा के लिए ये समूह अपने-अपने ढंग से सक्रिय रहते हैं, वहाँ सर्वाधिकारवाद अथवा साम्यवादी समाजों में ये समूह अपना स्वतंत्र महत्व नहीं रखते वरन् उनकी स्थिति राज्य के केवल ऐसे साधनों के रूप में होती हैं जिनका उद्देश्य राज्य द्वारा निर्धारित लक्ष्यों की पूर्ति में सहायक होना होता हैं। Keywords: दबाव समूह, भारत, लोकतंत्र, सर्वाधिकारवाद, भूमिका।